A high-performance near-pure zinc alloy and its preparation method and application
By using high-performance near-pure zinc alloys in zinc alloys, using trace alloy elements and large plastic deformation + rapid cooling technology to form a co-polarized structure, the challenges of zinc alloys in strength, biocompatibility and degradation are solved. High performance and stability are achieved.
Patent Information
- Application Number
- CN202410463951.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-04-17
- Publication Date
- 2024-12-31
- Estimated Expiration
- 2044-04-17
AI Technical Summary
Existing zinc alloys have challenges in improving strength and biocompatibility. High alloy element content leads to side effects, long-term degradation product residues and stress corrosion, making it difficult to meet the requirements of medically degradable metal materials.
High-performance near-pure zinc alloy is adopted to form a co-polarized structure by controlling the addition of trace alloy elements and large plastic deformation + rapid cooling process, which can avoid untimely metabolism of alloy elements and long-term residues of second-phase degradation products, and improve stress corrosion resistance and uniformity. Degradation performance.
It achieves the improvement of high yield strength, tensile strength and plastic deformation rate, while ensuring biocompatibility and uniform degradation, significantly improving the mechanical properties and stress corrosion resistance of zinc alloys.
Smart Images

Figure CN118389906B_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of zinc alloys and relates to a high-performance near-pure zinc alloy and a preparation method and application thereof. Background Art
[0002] Zinc is one of the essential trace elements for the human body. It has the functions of promoting the proliferation and differentiation of bone cells, anti-inflammatory and anti-thrombotic. Zinc has a suitable degradation rate, which meets the requirements of orthopedics and coronary implants. It can be gradually degraded after playing its role, avoiding the risks of secondary surgery to remove traditional materials or long-term risks of implants remaining in the body. Therefore, zinc is a potential new generation of medical degradable metal materials.
[0003] With the development of medical devices such as bone screws and coronary stents towards lightweight and high biocompatibility, higher requirements are placed on the strength, plasticity and stress corrosion resistance of materials. The mechanical properties of pure zinc are poor, with a strength of less than 100 MPa, which is far from the requirements of degradable metal implant medical devices. Alloying is one of the effective methods to improve the strength of pure zinc. The current strategy is to increase the strength by increasing the addition of alloying elements. For example, Tong et al. reported that the total amount of alloying elements in the Zn-4.5Ge alloy was 4.5 at.%, and the tensile strength was 237 MPa (X Tong, et al. Acta Biomaterialia, 2018, 82: 197-204.). E. Mostaed et al. reported that the total amount of alloying elements in the Zn-2.5Ag-0.6Mn alloy was 3.1 at.%, with a tensile strength of 302 MPa and an elongation of 35% (E Mostaed, et al. Acta Biomaterialia, 2020, 105: 319-335.). As the degree of alloying increases, the performance improves slowly, while the resource dependence and raw material cost of the material continue to increase. For example, Tang et al. reported that the tensile strength of Zn-3.1at.%Cu alloy was 257MPa and the elongation was 47%. When 2.6at.%Mg was added, the tensile strength increased to 440MPa, but the elongation was only 1%. At this time, the total amount of alloying elements reached 5.7at.% (ZB Tang, et al. Materials and Design, 2017, 117: 84-94.).
[0004] Following the existing design concept, it is feasible to increase the strength of zinc alloy by increasing the amount of alloying elements added. However, implanting devices made of highly alloyed zinc alloy into the human body is prone to the following problems:
[0005] (1) A large amount of alloying elements are released into the surrounding tissues, which may cause side effects if they are not metabolized in time;
[0006] (2) Alloying elements and Zn form intermetallic compound second phases, and their volume fraction increases with the content of alloying elements. Most of these second phases have a longer degradation cycle than the Zn matrix, which may cause the degradation products to remain in the body for a long time. On the other hand, these second phases form micro-galvanic couples with the Zn matrix, which accelerates the local corrosion of zinc alloys. A large amount of corrosion products cause the aggregation of inflammatory cells and macrophages, which cannot be cleared and reach a steady state in a short time, resulting in poor biocompatibility.
[0007] (3) Highly alloyed zinc alloys are prone to local corrosion due to the high content of second phases. In a stress corrosion environment, the stress field between the second phase and the Zn matrix leads to stress concentration and crack initiation, which aggravates local corrosion and becomes the key reason for premature failure of the device during service. For example, Bowen et al. implanted Zn-xAl (x = 2.4, 7, 11.3 at.%) alloys into the rat aorta. After 3 months of implantation, acute local inflammation with neutrophil and eosinophil infiltration was still observed. The higher the amount of Al added, the more obvious the inflammation. Zn-Al alloys exhibit intergranular corrosion during the service of the aorta, which can easily lead to implant rupture and failure. High doses of Al are not metabolized in time and can easily cause neurological toxicity (P K. Bowen, et al. Journal of Biomedical Materials Research, 2018, 106: 245-258.).
[0008] Therefore, how to break the limitations of existing design ideas and develop a medical degradable zinc alloy with high strength, high plasticity, stress corrosion resistance, excellent biocompatibility and uniform degradation while minimizing the amount of alloy elements added is a key issue that needs to be solved urgently. Summary of the invention
[0009] The national standard GB / T 470-2008 "Zinc Ingot" stipulates that zinc ingots are divided into 5 grades according to chemical composition, namely Zn99.995, Zn99.99, Zn99.95, Zn99.5 and Zn98.5, and their purities are 99.995%, 99.99%, 99.95%, 99.5% and 98.5% respectively. In view of the problems of high alloying element content (many intermetallic compound second phase particles), slow performance improvement, easy stress corrosion cracking and poor biocompatibility of existing zinc alloys, the present invention provides a high-performance near-pure zinc alloy and its preparation method and application, which ensures high purity of zinc (volume fraction of second phase particles ≤2%) while still having high performance. The "near-pure zinc alloy" has the following 3 characteristics:
[0010] (1) Composition is in atomic percentage (%), Zn content ≥ 99.5%, and the rest are trace alloying elements added artificially;
[0011] (2) Yield strength ≥ 250 MPa, tensile strength ≥ 320 MPa, elongation ≥ 25%, change in mechanical properties at room temperature within 1 year ≤ 5%, maximum bending force ≥ 2 kN, stress corrosion sensitivity factor ≤ 15%;
[0012] (3) High degradation uniformity. After immersion for 60 days, the size of the corrosion pit (i.e., equivalent diameter) is ≤15 μm, the standard deviation is ≤3 μm, and the uniformity coefficient of the corrosion pit distribution is ≥80%. The calculation formula of the uniformity coefficient η is as follows:
[0013]
[0014] Among them, p i is the number of corrosion pits in the i-th grid, is the average number of corrosion pits, and N is the number of grids.
[0015] The present invention is achieved through the following technical solutions:
[0016] The first aspect of the present invention is to provide a high performance "near pure zinc alloy",
[0017] The invention is characterized in that the composition is measured in atomic percentage (%), the Zn content is ≥99.5%, and the rest are trace alloying elements added artificially, including at least 2 of the following 14 elements: Mg, Mn, Li, Cu, Ag, Ca, Sr, Fe, Zr, Ti, Al, C, Ga, and Si.
[0018] The volume fraction of the second phase particles in the nearly pure zinc alloy is ≤2%, and the size of the second phase particles (ie, equivalent diameter) is ≤1 μm.
[0019] By controlling the amount of element addition and combining large plastic deformation + rapid cooling process, a co-segregated structure formed by two or more of the above 14 elements is constructed at defects such as grain boundaries, subgrain boundaries, twin boundaries, dislocations, etc. without forming other phases.
[0020] The total amount of alloying elements in the near-pure zinc alloy is ≤0.5%, which effectively avoids the problems of untimely metabolism of alloying elements, long-term residue of second phase and degradation products, and poor biocompatibility in highly alloyed zinc alloys.
[0021] The co-segregated structure formed by the various trace alloying elements in the near-pure zinc alloy has the following four functions:
[0022] (1) Effectively hinder dislocation movement and interface migration, significantly improve the strength of near-pure zinc alloys, and maintain good mechanical property stability;
[0023] (2) Strengthen the interface, improve the ability to resist stress corrosion and inhibit intergranular cracking;
[0024] (3) Stabilize the interface, so that the plastic deformation mode of the near-pure zinc alloy changes from dislocation slip to grain boundary deformation, significantly improving the plasticity of the near-pure zinc alloy;
[0025] (4) Weaken the micro-galvanic corrosion effect and significantly improve the degradation uniformity.
[0026] The microstructure of the "near pure zinc alloy" of the present invention has the following two characteristics:
[0027] (1) The average size of Zn grains is ≤2 μm, the volume fraction of second phase particles is ≤2%, the size of second phase particles (i.e. equivalent diameter) is ≤1 μm, and the dislocation density is ≤2×10 14 m -2 ;
[0028] (2) When kept at 37-200°C in an air atmosphere for 5-100 hours, the average size of the Zn grains is ≤10μm, with good organizational stability;
[0029] The recrystallization temperature of the "nearly pure zinc alloy" of the present invention is ≥80°C, which is significantly higher than the recrystallization temperature of pure zinc (i.e., 15°C);
[0030] The room temperature tensile properties of the "nearly pure zinc alloy" of the present invention are: yield strength 250-450MPa, tensile strength 320-650MPa, elongation 25%-185%;
[0031] After the "near pure zinc alloy" of the present invention is stored in air at 37°C for one year, the strength decreases by ≤5%, and the elongation decreases by ≤5%;
[0032] The maximum bending force of the "nearly pure zinc alloy" of the present invention is ≥2kN;
[0033] The room temperature compression performance of the "near pure zinc alloy" of the present invention is: the yield strength is 260-510 MPa, the stress when the compression deformation is 70% is 750-980 MPa, that is, the compressive strength is ≥750 MPa;
[0034] The degradation mode of the "nearly pure zinc alloy" of the present invention in simulated body fluid (SBF), Hank's, phosphate buffered saline (PBS), physiological saline and other solutions at 37°C is uniform degradation. After immersion for 60 days, the size of the corrosion pit (i.e., equivalent diameter) is ≤15 μm, the standard deviation is ≤3 μm, and the grid counting method analysis shows that the uniformity coefficient of the corrosion pit distribution is ≥80%, and the degradation rate is 0.02-1.8 mm / year;
[0035] The stress corrosion sensitivity factor of the "nearly pure zinc alloy" of the present invention is ≤15%;
[0036] The "near-pure zinc alloy" of the present invention has a cell survival rate of ≥80% for cells such as human aortic smooth muscle cells (HASMC), fibroblasts (human aortic adventitial fibroblasts, HAAF), endothelial cells (human umbilical vein endothelial cells, HUVEC), and mouse embryonic osteoblasts (MC3T3-E1), and an antibacterial activity of ≥90% for bacteria such as Escherichia coli and Staphylococcus aureus.
[0037] The second aspect of the present invention is to provide a method for preparing the near-pure zinc alloy.
[0038] The preparation method of the near-pure zinc alloy comprises: alloy smelting → heat treatment → large plastic deformation → rapid cooling;
[0039] The method of large plastic deformation + rapid cooling can induce the formation of a large number of defects (such as vacancies, grain boundaries, twin boundaries, etc.), and promote the formation of co-segregated structures of multiple alloy elements at defects such as grain boundaries and twin boundaries;
[0040] Preferably,
[0041] The alloy smelting process uses pure metals corresponding to each element in the near-pure zinc alloy as raw materials, wherein the raw material Zn is pure zinc with a purity greater than 99.99%, and is smelted 3 to 10 times under vacuum or inert gas protection to obtain a near-pure zinc alloy ingot, which can make the composition more uniform and reduce the formation of casting defects;
[0042] The smelting conditions are as follows: the alloy is smelted in a ceramic crucible such as Al2O3 with a melting point higher than 2000°C, and the principle of selecting the crucible material is to select a ceramic material with a melting point at least 800°C higher than that of pure zinc, so as to avoid chemical contamination of the alloy of the present invention by the crucible material; the smelting is carried out in two steps, firstly heating to 480-550°C, keeping warm for 1-3 minutes, and then cooling to 420-460°C, keeping warm for 1-5 minutes, so as to promote the co-segregation of alloy elements at the Zn grain boundary.
[0043] Electromagnetic stirring is applied during the smelting process to make the melt composition uniform, and the frequency of the electromagnetic stirring is 800-3000HZ; at least one melt covering agent selected from KCl, NaCl, MgCl2, LiCl, and borax is also added during the smelting process;
[0044] The heat treatment is at least one of homogenization heat treatment, solution heat treatment, aging heat treatment, and double-stage aging heat treatment.
[0045] Preferably,
[0046] The heat treatment includes but is not limited to the following four methods:
[0047] (1) Homogenization heat treatment;
[0048] (2) Solution heat treatment;
[0049] (3) Solution heat treatment first, followed by aging heat treatment;
[0050] (4) First perform solution heat treatment, then perform double-stage aging heat treatment;
[0051] Preferably,
[0052] The temperature of the homogenization heat treatment is 200-360°C, and the temperature is kept for 3-10 hours;
[0053] The temperature of the solution heat treatment is 300-360°C, and the temperature is kept for 8-20 hours;
[0054] The temperature of the aging heat treatment is 50 to 180° C., and the temperature is kept for 0.1 to 12 hours;
[0055] The first stage aging heat treatment temperature of the double-stage aging heat treatment is 50-80° C., and the insulation time is 5 min-6 h. The second stage aging heat treatment temperature is 100-150° C., and the insulation time is 5 min-10 h.
[0056] The cooling method after the heat treatment is any one of air cooling, furnace cooling, water quenching and oil quenching;
[0057] The large plastic deformation is selected from at least one of groove rolling, rolling, equal-channel angular extrusion, high-pressure torsion, and high-speed impact;
[0058] The temperature of the large plastic deformation is -50 to 320°C, and the temperature is kept for 15 minutes to 3 hours before deformation;
[0059] The single-pass deformation of the large plastic deformation is ≥20%, and the total deformation is ≥98%;
[0060] During the groove rolling, the rolling speed is 0.05-0.6 m / s; the deformation of a single pass is 20%-28%, and the total deformation is 98%-99%;
[0061] During the rolling, the deformation of a single rolling pass is 30% to 45%, the rolling speed is 0.5 to 2.5 m / s, and the total deformation is 98% to 99.5%;
[0062] During the equal-channel angular extrusion, the corresponding extrusion passes are 10 to 25, the extrusion speed is 1 to 20 mm / s, and the total deformation is 98% to 99.7%;
[0063] During the high-pressure twisting, the applied pressure is 0.5 to 6 GPa, the number of deformation circles is 2 to 6 circles, and the twisting speed is 0.3 to 2 r / min;
[0064] During the high-speed impact, the impact speed is 10-100 m / s, the impact load is 100-1000 N, the impact angle is 45-60°, and the impact time is 0.1-1 s.
[0065] The rapid cooling method after the large plastic deformation is any one of quenching in a water bath, an oil bath, and liquid nitrogen;
[0066] The third aspect of the present invention is to provide the application of the "near pure zinc alloy".
[0067] The near-pure zinc alloy of the present invention is suitable for preparing degradable stents such as coronary artery and other vascular stents, urethral stents, biliary stents, tracheal stents, esophageal stents, intestinal stents, porous bone defect filling stents and other lumen stents and bone tissue repair stents; it can also be used to prepare bone implant devices such as bone nails, bone needles, bone plates, wire anchors, screws, bone sleeves, bone connectors, bone clamps, etc.; it can also be used to prepare intestinal, vascular or neural anastomosis devices or anastomosis nails, vascular clamps, etc.; it can also be used to prepare guided bone regeneration membranes, guided tissue regeneration membranes, artificial heart valves, meningeal repair membranes, etc.; it can also be used to prepare soluble bridge plugs, soluble fracturing balls, etc. for oil drills, zinc alloy die-castings such as plate and shell parts, wear-resistant and shock-absorbing parts, electrogalvanized materials, building zinc materials, battery zinc materials, printing zinc materials, zinc-based alloy solders, etc.
[0068] The key points of the present invention are:
[0069] The deformation amount of the ordinary pure zinc metal plastic deformation process is ≤85%, and large plastic deformation and rapid cooling are not required, because large plastic deformation + rapid cooling process has no obvious effect on the performance of pure zinc metal after processing. The present invention adds trace alloy elements with a total amount not exceeding 0.5% on the basis of pure zinc metal, and promotes two or more elements of extremely trace Mg, Mn, Li, Cu, Ag, Ca, Sr, Fe, Zr, Ti, Al, C, Ga, Si with obvious segregation tendency to form a co-segregation structure at defects such as grain boundaries, subgrain boundaries, twin boundaries, dislocations, etc. through large plastic deformation + rapid cooling process without forming intermetallic compound second phase particles. As a result, the performance of the near-pure zinc alloy of the present invention has been greatly changed, which is significantly higher than that of pure zinc. The near-pure zinc alloy provided has high performance under the condition of extremely low alloy element addition: yield strength ≥250MPa, tensile strength ≥320MPa, elongation ≥25%, the range of change of mechanical properties stored at room temperature within 1 year ≤5%, the maximum bending force ≥2kN, the stress corrosion sensitivity factor ≤15%, uniform degradation, and the size of the corrosion pit (i.e., equivalent diameter) after 60 days of immersion ≤15μm, the standard deviation ≤3μm, and the uniformity coefficient of the corrosion pit distribution ≥80%; and the co-segregated structure formed by the near-pure zinc alloy of the present invention significantly improves the strength of the near-pure zinc alloy and maintains good mechanical property stability; at the same time, it improves the ability to resist stress corrosion and inhibit intergranular cracking; promotes the transformation of the plastic deformation mode from dislocation slip to grain boundary deformation, improves plasticity; weakens the galvanic corrosion effect and promotes uniform degradation.
[0070] Compared with the prior art, the present invention has at least the following characteristics and advantages:
[0071] 1. The total amount of alloying elements added in the near-pure zinc alloy of the present invention does not exceed 0.5%, and the content of Zn element in the alloy still meets the purity of pure zinc specified in the national standard GB / T 470-2008. However, the strength and mechanical property stability of the alloy of the present invention are significantly higher than those of pure zinc; the near-pure zinc alloy provided by the present invention has high performance under the condition of extremely low alloying element addition: yield strength ≥250MPa, tensile strength ≥320MPa, elongation ≥25%, change in mechanical properties at room temperature storage within 1 year ≤5%, maximum bending force ≥2kN, stress corrosion sensitivity factor ≤15%, uniform degradation, corrosion pit size (i.e. equivalent diameter) ≤15μm after immersion for 60 days, standard deviation ≤3μm, and uniformity coefficient of corrosion pit distribution ≥80%.
[0072] 2. The large plastic deformation + rapid cooling process provided by the present invention promotes two or more elements among extremely trace amounts of Mg, Mn, Li, Cu, Ag, Ca, Sr, Fe, Zr, Ti, Al, C, Ga, and Si with obvious segregation tendency to form a co-segregation structure at defects such as grain boundaries, subgrain boundaries, twin boundaries, and dislocations without forming intermetallic compound second phase particles.
[0073] 3. The co-segregated structure formed by the near-pure zinc alloy of the present invention significantly improves the strength of the near-pure zinc alloy and maintains good mechanical property stability; at the same time, it improves the ability to resist stress corrosion and inhibit intergranular cracking; promotes the transformation of the plastic deformation mode from dislocation slip to grain boundary deformation, improves plasticity; weakens the galvanic corrosion effect and promotes uniform degradation.
[0074] 4. The total amount of alloying elements in the near-pure zinc alloy of the present invention is low, the volume fraction of the second phase particles is ≤2%, and the size of the second phase particles (i.e., the equivalent diameter) is ≤1 μm, which effectively avoids the problems of untimely metabolism of alloying elements, long-term residue of the second phase and degradation products, and poor biocompatibility in highly alloyed zinc alloys.
[0075] 5. The average grain size of the Zn crystals of the near-pure zinc alloy of the present invention is ≤2μm, and the dislocation density is ≤2×10 14 m -2 , kept warm for 5h to 100h in an air atmosphere at 37 to 200°C, the average size of the Zn grains is ≤10μm, and the alloy has good organizational stability; the recrystallization temperature of the near-pure zinc alloy of the present invention is ≥80°C, which is significantly higher than the recrystallization temperature of pure zinc (i.e., 15°C).
[0076] 6. The preparation method provided by the present invention is easy to realize industrial batch production. BRIEF DESCRIPTION OF THE DRAWINGS
[0077] In order to more clearly illustrate the technical solutions in the embodiments of the present invention, the following briefly introduces the drawings required for use in the description of the embodiments. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without creative work.
[0078] Figure 1 This is a microstructure diagram of the co-segregation of Mn and Mg elements at the grain boundaries in the near-pure zinc alloy 2 prepared in Example 2 of the present invention (wherein the elliptical frame represents the co-segregation area).
[0079] Figure 2 This is a zinc grain structure diagram of the near-pure zinc alloy 5 prepared in Example 5 of the present invention.
[0080] Figure 3 This is a bar chart of the tensile mechanical properties of the near-pure zinc alloy 2 prepared in Example 2 of the present invention.
[0081] Figure 4 It is a comparison chart of the maximum bending force of Example 8 of the present invention and the comparative example of pure zinc.
[0082] Figure 5 This is a morphology of corrosion pits after the nearly pure zinc alloy 10 prepared in Example 10 of the present invention was immersed in simulated body fluid (SBF) at 37° C. for 60 days and the corrosion products were removed. DETAILED DESCRIPTION
[0083] In order to make the technical problems, technical solutions and advantages to be solved by the present invention more clear, a detailed description will be given below with reference to the accompanying drawings and specific embodiments.
[0084] Test method:
[0085] Near-pure zinc alloys were tested for recrystallization temperature, room temperature tensile mechanical properties, room temperature bending properties, corrosion rate, biocompatibility and stress corrosion susceptibility.
[0086] Among them, the recrystallization temperature is evaluated by combining metallographic method and hardness method;
[0087] Evaluate the room temperature tensile mechanical properties according to GB / T228.1-2010 "Tensile test of metallic materials Part 1: Room temperature test method";
[0088] The room temperature bending properties were evaluated according to GB / T 1449.5-2005 "Metallic materials - Tensile tests Part 5: Three-point bending test method at room temperature";
[0089] Evaluate the corrosion rate according to ASTM G31-72 "Standard Guide for Laboratory Immersion Corrosion Testing of Metals";
[0090] Evaluate biocompatibility according to GB / T16886 "Biological Evaluation of Medical Devices Part 5: In Vitro Cytotoxicity Test";
[0091] The stress corrosion sensitivity is evaluated according to GB / T 15970.1-2018 "Corrosion stress corrosion test of metals and alloys".
[0092] Examples 1-15
[0093] Composition, preparation and performance testing of high performance ternary near-pure zinc alloy.
[0094] The chemical compositions of 15 embodiments of the high performance ternary near-pure zinc alloy composition are shown in Table 1-1. The preparation and processing flow of the near-pure zinc alloy is: alloy smelting → homogenization heat treatment → groove rolling → water quenching.
[0095] The ingredients are prepared according to the ingredients of Example 1-15 shown in Table 1-1, wherein the raw material Zn is pure zinc with a purity greater than 99.99%, and is repeatedly smelted 5 times in an induction heating furnace under argon protection to obtain the corresponding near-pure zinc alloy ingot; the alloy is smelted in a ceramic crucible such as Al2O3 with a melting point higher than 2000°C, and the principle of selecting the crucible material is to use a ceramic material with a melting point at least 800°C higher than that of pure zinc, so as to avoid chemical contamination of the alloy of the present invention by the crucible material; the smelting is carried out in two steps, firstly heating to 500°C and keeping warm for 1 minute, and then cooling to 420°C and keeping warm for 1 minute, so as to promote the co-aggregation of alloy elements at the Zn grain boundary; then the alloy melt is poured into a mold and cooled to room temperature.
[0096] Electromagnetic stirring is applied during the smelting process, wherein the frequency of the electromagnetic stirring is 900HZ, which is beneficial to improving the purity and quality of the near-pure zinc alloy ingot; KCl melt covering agent is also added during the smelting process, which is beneficial to reducing metal oxidation and the formation of impurities and improving the purity of the near-pure zinc alloy ingot.
[0097] The temperature of the homogenization heat treatment is 360°C, which is kept for 6 hours and then cooled in the furnace.
[0098] The groove rolling temperature is 200°C, the pre-rolling insulation is 0.5h, the rolling speed is 0.2m / s, the single-pass deformation is 25% to 30%, and the total deformation is 98%; since the invention alloy 1-15 in Table 1-1 has good processability, no annealing is required between rolling passes, and the surface quality of the finally obtained rolled wire is good, and no cracks appear on the surface; in comparison, cracks appear on the surface of Zn-0.4Li and Zn-0.8Li alloy wires prepared by the same method.
[0099] Water quenching is performed immediately after the groove rolling is completed. On the one hand, it promotes the co-segregation of alloy elements at the Zn grain boundary, and on the other hand, it inhibits the growth of zinc grains and avoids the reduction of alloy strength.
[0100] The microstructures of the nearly pure zinc alloys of Examples 1 to 15 in Table 1-1 were observed using a transmission electron microscope (TEM), and it was found that the added alloying elements co-segregated at the grain boundaries. The TEM microstructure of the co-segregation of Mn and Mg elements at the grain boundaries in Example Inventive Alloy 2 is shown in FIG. Figure 1 As shown; no grain boundary segregation phenomenon was found in the comparative examples Zn-0.6Mn, Zn-0.8Mn and Zn-1Mn alloys prepared by the same method.
[0101] The microstructures of the nearly pure zinc alloys of Examples 1-15 in Table 1-1 were observed by electron backscatter diffraction (EBSD), and it was found that the average Zn grain size of these inventive alloys was ≤1.5 μm, the volume fraction of the second phase particles was ≤1.6%, the size of the second phase particles (i.e., the equivalent diameter) was ≤1 μm, and the dislocation density was ≤1.5×1014 m -2 ; After being kept in air at 100°C for 10 hours, the average Zn grain size of the invention alloys of Examples 1-15 is ≤2μm, and has good structural stability; the Zn grain size of the invention alloy 5 of Example 1-1 is as follows Figure 2 shown.
[0102] The recrystallization temperature of the near-pure zinc alloy of Example 1-15 in Table 1-1 was measured to be 80-120° C. The recrystallization temperature of the comparative pure zinc prepared by the same method was 15-25° C. This shows that the trace elements added to the near-pure zinc alloy can significantly increase the recrystallization temperature of the zinc matrix.
[0103] The room temperature tensile properties of the near-pure zinc alloy of Example 1-15 in Table 1-1 were measured as follows: yield strength 250-405 MPa, tensile strength 320-500 MPa, elongation 25%-156%; after being stored in air at 37°C for one year, the strength reduction was ≤3%, and the elongation reduction was ≤5%; the room temperature tensile properties of the comparative pure zinc prepared by the same method were as follows: yield strength 30-50 MPa, tensile strength 80-120 MPa, elongation 5%-35%, and the strength reduction was ≥40% after being stored in air at 37°C for one year. It can be seen that the co-segregated structure on the Zn grain boundary in the near-pure zinc alloy of Example 1-15 can significantly improve the room temperature mechanical properties of the material and maintain the stability of the mechanical properties. The tensile mechanical properties of the inventive alloy 2 of Example are shown in FIG. Figure 3 shown.
[0104] The maximum bending force of the near-pure zinc alloy of Example 1-15 in Table 1-1 was measured to be 2.3-5 kN, and the maximum bending force of the comparative pure zinc, Zn-1Mn, Zn-1.5Cu, Zn-0.6Fe, Zn-0.6Ca and other alloys prepared by the same method was ≤0.8 kN. The maximum bending force comparison of the inventive alloy 8 and the comparative pure zinc is shown in the figure below. Figure 4 shown.
[0105] It was measured that the degradation mode of the near-pure zinc alloy of Example 1-15 in Table 1-1 in SBF at 37°C is uniform degradation. After immersion for 60 days, the size of the corrosion pit (i.e., equivalent diameter) is ≤8μm, the standard deviation is ≤1.2μm, the uniformity coefficient of the corrosion pit distribution is ≥89%, and the degradation rate is 0.02-0.5mm / y. The degradation mode of the comparative example pure zinc, Zn-0.6Mn, Zn-0.8Mn, Zn-1Mn, Zn-1Cu, Zn-2Cu, Zn-0.8Fe, Zn-0.8Ca and other alloys prepared by the same method in SBF at 37°C is local corrosion. After immersion for 60 days, the size of the corrosion pit (i.e., equivalent diameter) is ≥35μm, the standard deviation is ≥15μm, and the uniformity coefficient of the corrosion pit distribution is ≤50%. After immersion in SBF at 37°C for 60 days, the morphology of the corrosion pit after removing the corrosion product of Example Inventive Alloy 10 is as follows: Figure 5 shown.
[0106] It was measured that the stress corrosion sensitivity factor of the near-pure zinc alloy of Example 1-15 in Table 1-1 was ≤10%, and the stress corrosion sensitivity factor of the comparative pure zinc, Zn-0.6Mn, Zn-0.8Mn, Zn-1Mn, Zn-1Cu, Zn-2Cu, Zn-0.8Fe, Zn-0.8Ca and other alloys prepared by the same method was ≥20%.
[0107] It was measured that the cell survival rate of the near-pure zinc alloy of Example 1-15 in Table 1-1 on human aortic smooth muscle cells (HASMC), endothelial cells (human umbilical vein endothelial cells, HUVEC), and mouse embryonic osteoblasts (MC3T3-E1) was ≥80%, and the antibacterial activity against Escherichia coli and Staphylococcus aureus was ≥90%.
[0108] The properties of the near-pure zinc alloys of some embodiments and comparative examples are shown in Table 1-2.
[0109] Table 1-1
[0110]
[0111] Table 1-2
[0112]
[0113] Embodiment 16-30
[0114] Composition, preparation and property testing of high performance quaternary near-pure zinc alloy.
[0115] The chemical compositions of 15 examples of the high performance quaternary near-pure zinc alloy composition are shown in Table 2-1. The preparation and processing flow of the near-pure zinc alloy is: alloy smelting → solution heat treatment → groove rolling → water quenching → rolling → oil quenching.
[0116] The ingredients are prepared according to the ingredients of Examples 16-30 shown in Table 2-1, wherein the raw material Zn is pure zinc with a purity greater than 99.99%, and is repeatedly smelted 6 times in an induction heating furnace under argon protection to obtain the corresponding near-pure zinc alloy ingot; the alloy is smelted in a ceramic crucible such as Al2O3 with a melting point higher than 2000°C, and the principle of selecting the crucible material is to use a ceramic material with a melting point at least 800°C higher than that of pure zinc, so as to avoid chemical contamination of the alloy of the present invention by the crucible material; the smelting is carried out in two steps, firstly heating to 510°C and keeping warm for 2 minutes, then cooling to 430°C and keeping warm for 1 minute, so as to promote the co-aggregation of alloy elements at the Zn grain boundary; then the alloy melt is poured into a mold and cooled to room temperature.
[0117] Electromagnetic stirring is applied during the smelting process, wherein the frequency of the electromagnetic stirring is 1000HZ, which is beneficial to improving the purity and quality of the near-pure zinc alloy ingot; a NaCl melt covering agent is also added during the smelting process, which is beneficial to reducing metal oxidation and the formation of impurities and improving the purity of the near-pure zinc alloy ingot.
[0118] The solution heat treatment temperature is 360℃, and the mixture is kept at this temperature for 16h before being water quenched.
[0119] The groove rolling temperature is 230°C, the heat preservation before rolling is 1h, the rolling speed is 0.3m / s, the deformation of a single pass is 28% to 35%, and the total deformation is 98%; since the invention alloy 16-30 in Table 2-1 has good processability, no annealing is required between rolling passes, and the surface quality of the finally obtained rolled wire is good, and no cracks appear on the surface; in comparison, cracks appear on the surface of Zn-0.8Ca and Zn-1Fe alloy wires prepared by the same method.
[0120] Water quenching is performed immediately after the groove rolling is completed. On the one hand, it promotes the co-segregation of alloy elements at the Zn grain boundary, and on the other hand, it inhibits the growth of zinc grains and avoids the reduction of alloy strength.
[0121] The rolling temperature is 200℃, the temperature is kept for 30 minutes before rolling, the rolling speed is 1m / s, the deformation of a single pass is 32% to 37%, and the total deformation is 99%. Oil quenching is performed immediately after rolling is completed.
[0122] The microstructure of the near-pure zinc alloys in the examples in Table 2-1 was observed using a transmission electron microscope (TEM), and it was found that the added alloying elements co-segregated at the grain boundaries; no grain boundary segregation was found in the comparative examples Zn-0.6Ag, Zn-0.8Ag and Zn-1Ag alloys prepared by the same method.
[0123] Electron backscatter diffraction (EBSD) was used to observe the microstructure of the near-pure zinc alloy of Examples 16-30 in Table 2-1, and it was found that the average size of the Zn grains was ≤1.2 μm, the volume fraction of the second phase particles was ≤2%, the size of the second phase particles (i.e., the equivalent diameter) was ≤1 μm, and the dislocation density was ≤1.5×10 14 m -2 ; When kept at 120℃ in air atmosphere for 50h, the average size of Zn grains is ≤4μm, with good organizational stability.
[0124] The recrystallization temperature of the near-pure zinc alloy of Examples 16-30 in Table 2-1 was measured to be 86-130° C. The recrystallization temperature of the pure zinc of the comparative example prepared by the same method was 15-26° C., which shows that the trace elements added to the near-pure zinc alloy can significantly increase the recrystallization temperature of the zinc matrix.
[0125] The room temperature tensile properties of the near-pure zinc alloy of Example 16-30 in Table 2-1 are measured as follows: yield strength 270-420MPa, tensile strength 340-530MPa, elongation 28%-161%; after being stored in air at 37°C for one year, the strength reduction is ≤2%, and the elongation reduction is ≤4%; the room temperature tensile properties of the comparative pure zinc prepared by the same method are as follows: yield strength 30MPa-45MPa, tensile strength 68MPa-110MPa, elongation 5%-30%; after being stored in air at 37°C for one year, the strength reduction is ≥46%, and the elongation reduction is ≥35%. It can be seen that the co-segregated structure on the Zn grain boundary in the near-pure zinc alloy of Example 16-30 can significantly improve the room temperature mechanical properties of the material and maintain the stability of the mechanical properties.
[0126] The maximum bending force of the near-pure zinc alloys of Examples 16-30 in Table 2-1 was measured to be 2.5-5 kN, and the maximum bending force of the comparative pure zinc, Zn-1Mn, Zn-1Cu, Zn-1Fe and other alloys prepared by the same method was ≤0.7 kN.
[0127] It was measured that the degradation mode of the near-pure zinc alloys of Examples 16-30 in Table 2-1 in SBF at 37°C was uniform degradation. After immersion for 60 days, the corrosion pit size (i.e., equivalent diameter) was ≤12μm, the standard deviation was ≤1.2μm, and the degradation rate was 0.04-0.6mm / y. The degradation mode of the comparative examples pure zinc, Zn-0.7Mn, Zn-1Mn, Zn-2Cu, Zn-3Cu, Zn-0.6Fe, Zn-0.6Ca and other alloys prepared by the same method in SBF at 37°C was local corrosion. After immersion for 60 days, the corrosion pit size (i.e., equivalent diameter) was ≥40μm, the standard deviation was ≥18μm, and the uniformity coefficient of corrosion pit distribution was ≤45%.
[0128] It was measured that the stress corrosion sensitivity factor of the near-pure zinc alloys of Examples 16-30 in Table 2-1 was ≤8%, and the stress corrosion sensitivity factor of the comparative examples pure zinc, Zn-0.6Ag, Zn-0.8Mn, Zn-1Mn, Zn-0.6Fe, and Zn-0.8Cu prepared by the same method was ≥25%.
[0129] It was measured that the cell compatibility of the near-pure zinc alloy of Example 16-30 in Table 2-1 to human aortic smooth muscle cells (HASMC), fibroblasts (human aortic adventitial fibroblasts, HAAF), endothelial cells (human umbilical vein endothelial cells, HUVEC), and mouse embryonic osteoblasts (MC3T3-E1) was ≥80%, and the antibacterial activity to Escherichia coli and Staphylococcus aureus was ≥90%.
[0130] The properties of the near-pure zinc alloys of some embodiments and comparative examples are shown in Table 2-2.
[0131] Table 2-1
[0132] Example Alloy composition (atomic percentage %) Example 16 Zn-0.4Li-0.05Mn-0.03Mg Embodiment 17 Zn-0.25Mg-0.05Li-0.008Mn Embodiment 18 Zn-0.25Mn-0.1Mg-0.006Li Embodiment 19 Zn-0.3Li-0.05Ca-0.004Mg Embodiment 20 Zn-0.3Al-0.1Mg-0.08Ca Embodiment 21 Zn-0.2C-0.2Ga-0.06Ti Embodiment 22 Zn-0.1Si-0.1Ca-0.15Ti Embodiment 23 Zn-0.4Li-0.05Sr-0.05Mn Embodiment 24 Zn-0.3Cu-0.1Mg-0.02Fe Embodiment 25 Zn-0.1Ag-0.1Ca-0.1Zr Embodiment 26 Zn-0.2Mg-0.15Ca-0.02Cu Embodiment 27 Zn-0.15Zr-0.1Ca-0.05Sr Embodiment 28 Zn-0.15Fe-0.05Ti-0.008Cu Embodiment 29 Zn-0.45Mg-0.02Ca-0.02Ga Embodiment 30 Zn-0.15Sr-0.12C-0.02Si
[0133] Table 2-2
[0134]
[0135]
[0136] Examples 31-45
[0137] Composition, preparation and performance testing of high performance pentyl near-pure zinc alloy.
[0138] The chemical compositions of 15 embodiments of the high performance five-element near-pure zinc alloy are shown in Table 3-1. The preparation and processing flow of the near-pure zinc alloy is: alloy smelting → solution heat treatment → aging heat treatment → high pressure torsion → water quenching.
[0139] The ingredients are prepared according to the ingredients of Examples 31-45 shown in Table 3-1, wherein the raw material Zn is pure zinc with a purity greater than 99.99%, and is repeatedly smelted 7 times in an induction heating furnace under argon protection to obtain the corresponding near-pure zinc alloy ingot; the alloy is smelted in a ceramic crucible such as Al2O3 with a melting point higher than 2000°C, and the principle of selecting the crucible material is to use a ceramic material with a melting point at least 800°C higher than that of pure zinc, so as to avoid chemical contamination of the alloy of the present invention by the crucible material; the smelting is carried out in two steps, firstly heating to 510°C and keeping warm for 1 minute, then cooling to 430°C and keeping warm for 2 minutes, so as to promote the co-aggregation of alloy elements at the Zn grain boundary; then the alloy melt is poured into a mold and cooled to room temperature.
[0140] Electromagnetic stirring is applied during the smelting process, wherein the frequency of the electromagnetic stirring is 1200HZ, which is beneficial to improving the purity and quality of the near-pure zinc alloy ingot; MgCl2 melt covering agent is also added during the smelting process, which is beneficial to reducing metal oxidation and the formation of impurities and improving the purity of the near-pure zinc alloy ingot.
[0141] The solution heat treatment temperature is 360℃, and the mixture is kept at this temperature for 20h before being water quenched.
[0142] The aging heat treatment temperature is 100°C and the insulation time is 0.1 to 6 hours.
[0143] The high-pressure torsion temperature was 260°C, the temperature was kept for 30 minutes before deformation, the applied pressure was 2 GPa, the number of deformation circles was 3 circles, and the torsion speed was 1 r / min.
[0144] Water quenching is performed immediately after high-pressure torsion is completed. On the one hand, it promotes the co-segregation of alloy elements at the Zn grain boundary, and on the other hand, it inhibits the growth of zinc grains and avoids the reduction of alloy strength.
[0145] The microstructure of the near-pure zinc alloys of Examples 31-45 in Table 3-1 was observed using a transmission electron microscope (TEM), and it was found that the added alloying elements co-segregated at the grain boundaries; no grain boundary segregation phenomenon was found in the comparative examples Zn-0.6Ag, Zn-0.8Ca and Zn-1Mn alloys prepared by the same method.
[0146] Electron backscatter diffraction (EBSD) was used to observe the microstructure of the near-pure zinc alloys of Examples 31-45 in Table 3-1, and it was found that the average size of the Zn grains was ≤1 μm, the volume fraction of the second phase particles was ≤2%, the size of the second phase particles (i.e., the equivalent diameter) was ≤1 μm, and the dislocation density was ≤1.8×10 14 m -2 ; When kept at 160℃ in air atmosphere for 15h, the average size of Zn grains is ≤3μm, with good organizational stability.
[0147] The recrystallization temperature of the near-pure zinc alloys of Examples 31-45 in Table 3-1 was measured to be 95-138° C. The recrystallization temperature of the pure zinc of the comparative example prepared by the same method was 15-28° C., which shows that the trace elements added to the near-pure zinc alloy can significantly increase the recrystallization temperature of the zinc matrix.
[0148] The room temperature tensile properties of the near-pure zinc alloys of Examples 31-45 in Table 3-1 are measured as follows: yield strength 280-430MPa, tensile strength 350-550MPa, elongation 25%-148%; after being stored in air at 37°C for one year, the strength reduction is ≤2%, and the elongation reduction is ≤5%; the room temperature tensile properties of the pure zinc of the comparative example prepared by the same method are as follows: yield strength 40MPa-48MPa, tensile strength 70MPa-115MPa, elongation 2%-30%; after being stored in air at 37°C for one year, the strength reduction is ≥45%, and the elongation reduction is ≥33%. It can be seen that the co-segregated structure on the Zn grain boundary of the near-pure zinc alloys of Examples 31-45 can significantly improve the room temperature mechanical properties of the material and maintain the stability of the mechanical properties.
[0149] The maximum bending force of the near-pure zinc alloys of Examples 31-45 in Table 3-1 was measured to be 2.6-5.3 kN, and the maximum bending force of the comparative pure zinc, Zn-0.8Mn, Zn-1Cu, Zn-1Ca, Zn-0.6Ga, Zn-0.6Al and other alloys prepared by the same method was ≤0.7 kN.
[0150] It was measured that the degradation mode of the near-pure zinc alloys of Examples 31-45 in Table 3-1 in SBF at 37°C was uniform degradation. After immersion for 60 days, the corrosion pit size (i.e., equivalent diameter) was ≤13μm, the standard deviation of the corrosion pit size was ≤1.8μm, and the degradation rate was 0.07-0.8mm / y. The degradation mode of the comparative examples of pure zinc, Zn-1Mn, Zn-1Zr, Zn-0.8Sr, Zn-0.8Cu, Zn-0.8Ag and other alloys prepared by the same method was local corrosion in SBF at 37°C. After immersion for 60 days, the corrosion pit size (i.e., equivalent diameter) was ≥42μm, the standard deviation was ≥20μm, and the uniformity coefficient of corrosion pit distribution was ≤40%.
[0151] It was measured that the stress corrosion sensitivity factor of the near-pure zinc alloys of Examples 31-45 in Table 3-1 was ≤7%, and the stress corrosion sensitivity factor of the comparative pure zinc, Zn-1Mn, Zn-1Zr, Zn-0.8Sr, Zn-0.8Cu, Zn-0.8Ag, Zn-1Ca and other alloys prepared by the same method was ≥40%.
[0152] It was measured that the cell survival rate of the near-pure zinc alloys of Examples 31-45 in Table 3-1 for human aortic smooth muscle cells (HASMC), endothelial cells (human umbilical vein endothelial cells, HUVEC), and mouse embryonic osteoblasts (MC3T3-E1) was ≥80%, and the antibacterial activity against Escherichia coli and Staphylococcus aureus was ≥90%.
[0153] The properties of the near-pure zinc alloys of some embodiments and comparative examples are shown in Table 3-2.
[0154] Table 3-1
[0155] Example Alloy composition (atomic percentage %) Embodiment 31 Zn-0.08Ag-0.05Li-0.05Mn-0.03Mg Embodiment 32 Zn-0.1Mg-0.05Ca-0.05Sr-0.008Mn Embodiment 33 Zn-0.1Mn-0.1Li-0.05Zr-0.002Ti Embodiment 34 Zn-0.2Li-0.15Cu-0.05Mg-0.01Ca Embodiment 35 Zn-0.3Cu-0.05Mg-0.05Ca-0.02Fe Embodiment 36 Zn-0.1Ag-0.1Mn-0.1Li-0.04Ti Embodiment 37 Zn-0.1Mn-0.08Ti-0.08Ca-0.06Mg Embodiment 38 Zn-0.3Al-0.05Sr-0.05Mg-0.02Zr Embodiment 39 Zn-0.1Cu-0.1Mg-0.05Ca-0.05Fe Embodiment 40 Zn-0.3Ag-0.1Ca-0.05Zr-0.02Sr Embodiment 41 Zn-0.2Mg-0.2Cu-0.05Ca-0.02Fe Embodiment 42 Zn-0.15Zr-0.1Ca-0.05Sr-0.05Ga Embodiment 43 Zn-0.15Fe-0.1Cu-0.08Ca-0.05Ti Embodiment 44 Zn-0.3Mg-0.1Li-0.05Ca-0.02Ti Embodiment 45 Zn-0.1C-0.1Zr-0.05Sr-0.03Ca
[0156] Table 3-2
[0157]
[0158] Examples 46-52
[0159] Composition, preparation and performance testing of high performance multi-component near-pure zinc alloys.
[0160] The chemical compositions of 15 examples of the high-performance multi-element near-pure zinc alloy composition are shown in Table 4-1, where "multi-element" means that the alloy composition contains at least 6 elements. The preparation and processing flow of the near-pure zinc alloy is: alloy smelting → solution heat treatment → two-stage aging heat treatment → equal-diameter angular extrusion → water quenching.
[0161] The ingredients are prepared according to the ingredients of Examples 46-60 shown in Table 4-1, wherein the raw material Zn is pure zinc with a purity greater than 99.99%, and is repeatedly smelted 8 times in an induction heating furnace under argon protection to obtain the corresponding near-pure zinc alloy ingot; the alloy is smelted in a ceramic crucible such as Al2O3 with a melting point higher than 2000°C, and the principle of selecting the crucible material is to use a ceramic material with a melting point at least 800°C higher than that of pure zinc, so as to avoid chemical contamination of the alloy of the present invention by the crucible material; the smelting is carried out in two steps, firstly heating to 520°C and keeping warm for 3 minutes, and then cooling to 420°C and keeping warm for 3 minutes, so as to promote the co-aggregation of alloy elements at the Zn grain boundary; then the alloy melt is poured into a mold and cooled to room temperature.
[0162] Electromagnetic stirring is applied during the smelting process, wherein the frequency of the electromagnetic stirring is 1500HZ, which is beneficial to improving the purity and quality of the near-pure zinc alloy ingot; a borax melt covering agent is also added during the smelting process, which is beneficial to reducing metal oxidation and the formation of impurities and improving the purity of the near-pure zinc alloy ingot.
[0163] The solution heat treatment temperature is 360℃, and the mixture is kept at this temperature for 20h before being water quenched.
[0164] The first stage aging heat treatment temperature of the double-stage aging heat treatment is 60°C, the holding time is 1h, and the second stage aging heat treatment temperature is 100°C, the holding time is 3h.
[0165] The temperature of the equal-channel angular extrusion is 260°C, the number of extrusion passes is 15 to 25, the extrusion speed is 10 mm / s, and the total deformation is 99.5%. Since the invention alloy 46-60 in Table 4-1 has good processing formability, no annealing is required between equal-channel angular extrusion passes, and the surface quality of the wire obtained is good, and no cracks appear on the surface; in contrast, cracks appear on the surface of the Zn-0.6Fe and Zn-0.8Sr alloy wires prepared by the same method.
[0166] Water quenching is performed immediately after equal channel angular extrusion, which, on the one hand, promotes the co-segregation of alloy elements at the Zn grain boundary, and on the other hand, inhibits the growth of zinc grains and avoids the reduction of alloy strength.
[0167] The microstructures of the near-pure zinc alloys of Examples 46-60 in Table 4-1 were observed using a transmission electron microscope (TEM), and it was found that the added alloying elements co-segregated at the grain boundaries. No grain boundary segregation was found in the comparative examples Zn-0.8Ca, Zn-0.8Mn and Zn-1Fe alloys prepared in the same way.
[0168] Electron backscatter diffraction (EBSD) was used to observe the microstructure of the near-pure zinc alloys of Examples 46-60 in Table 4-1, and it was found that the average size of the Zn grains was ≤1 μm, the volume fraction of the second phase particles was ≤2%, the size of the second phase particles (i.e., the equivalent diameter) was ≤1 μm, and the dislocation density was ≤1.9×10 14 m -2 ; After being kept at 200℃ in air atmosphere for 26h, the average size of Zn grains is ≤3μm, with good organizational stability.
[0169] The recrystallization temperature of the near-pure zinc alloys of Examples 46-60 in Table 4-1 was measured to be 100-146° C. The recrystallization temperature of the pure zinc in the comparative example prepared by the same method was 15-30° C., which shows that the trace elements added to the near-pure zinc alloy can significantly increase the recrystallization temperature of the zinc matrix.
[0170] The room temperature tensile properties of the near-pure zinc alloys of Examples 46-60 in Table 4-1 are measured as follows: yield strength 300-450MPa, tensile strength 380-580MPa, elongation 25%-95%; after being stored in air at 37°C for one year, the strength reduction is ≤2%, and the elongation reduction is ≤5%; the room temperature tensile properties of the comparative pure zinc prepared by the same method are as follows: yield strength 40MPa-60MPa, tensile strength 70MPa-130MPa, elongation 5%-35%; after being stored in air at 37°C for one year, the strength reduction is ≥50%, and the elongation reduction is ≥38%. It can be seen that the co-segregated structure on the Zn grain boundary in the near-pure zinc alloys of Examples 46-60 can significantly improve the room temperature mechanical properties of the material and maintain the stability of the mechanical properties.
[0171] The maximum bending force of the near-pure zinc alloys of Examples 46-60 in Table 4-1 was measured to be 2.8-5.5 kN, and the maximum bending force of the comparative pure zinc, Zn-0.8Ca, Zn-1Fe, Zn-0.6Si, Zn-0.6Al and other alloys prepared by the same method was ≤0.5 kN.
[0172] It was measured that the degradation mode of the near-pure zinc alloys of Examples 46-60 in Table 4-1 in SBF at 37°C was uniform degradation. After immersion for 60 days, the corrosion pit size (i.e., equivalent diameter) was ≤15μm, the standard deviation of the corrosion pit size was ≤3μm, and the degradation rate was 0.07-1.5mm / y. The degradation mode of the comparative examples pure zinc, Zn-0.6Ti, Zn-0.8Zr, Zn-1Mn, Zn-1Ga, Zn-2Al, Zn-0.8Si, Zn-0.8C and other alloys prepared by the same method in SBF at 37°C was local corrosion. After immersion for 60 days, the corrosion pit size (i.e., equivalent diameter) was ≥45μm, the standard deviation was ≥30μm, and the uniformity coefficient of corrosion pit distribution was ≤46%.
[0173] It was measured that the stress corrosion sensitivity factor of the near-pure zinc alloys of Examples 46-60 in Table 4-1 was ≤6%, and the stress corrosion sensitivity factor of the comparative pure zinc, Zn-0.8Sr, Zn-1Mn, Zn-1Ga, Zn-5Al, Zn-1Si, Zn-0.8C and other alloys prepared by the same method was ≥42%.
[0174] It was measured that the cell survival rate of the near-pure zinc alloys of Examples 46-60 in Table 4-1 for human aortic smooth muscle cells (HASMC), endothelial cells (human umbilical vein endothelial cells, HUVEC), and mouse embryonic osteoblasts (MC3T3-E1) was ≥80%, and the antibacterial activity against Escherichia coli and Staphylococcus aureus was ≥90%.
[0175] The properties of the near-pure zinc alloys of some embodiments and comparative examples are shown in Table 4-2.
[0176] Table 4-1
[0177]
[0178] Table 4-2
[0179]
Claims
1. A high performance near-pure zinc alloy, characterized in that: The near-pure zinc alloy composition is measured in atomic percentage, with a Zn content of ≥99.5%, and the rest being trace alloying elements added artificially; The composition of the nearly pure zinc alloy is calculated by atomic percentage, and the total amount of artificially added alloying elements is ≤0.5%, including at least 2 of the following 14 elements: Mg, Mn, Li, Cu, Ag, Ca, Sr, Fe, Zr, Ti, Al, C, Ga, Si; The nearly pure zinc alloy forms a co-segregated structure of two or more elements of Mg, Mn, Li, Cu, Ag, Ca, Sr, Fe, Zr, Ti, Al, C, Ga, and Si at grain boundaries, subgrain boundaries, twin boundaries, and dislocation defects without forming intermetallic compound second phase particles; The preparation method of the near-pure zinc alloy comprises: alloy smelting→heat treatment→large plastic deformation→rapid cooling, and electromagnetic stirring is applied during the smelting process; the deformation amount of a single pass of the large plastic deformation is ≥20%, and the total deformation amount is ≥98%; The yield strength of the near-pure zinc alloy is ≥250 MPa, the tensile strength is ≥320 MPa, the elongation is ≥25%, the change range of mechanical properties in room temperature storage within 1 year is ≤5%, the maximum bending force is ≥2 kN, and the stress corrosion sensitivity factor is ≤15%; the degradation uniformity of the near-pure zinc alloy is high, and the size of the corrosion pit after immersion for 60 days, i.e., the equivalent diameter is ≤15 μm, the standard deviation is ≤3 μm, and the uniformity coefficient of the corrosion pit distribution is ≥80%; The uniformity coefficient η The calculation formula is as follows: (1) in, p i For the i The number of corrosion pits in a grid, is the average number of corrosion pits, N is the number of grids.
2. The high performance near-pure zinc alloy according to claim 1, characterized in that: The volume fraction of the second phase particles in the nearly pure zinc alloy is ≤2%, and the size of the second phase particles, that is, the equivalent diameter, is ≤1 mm.
3. The high performance near-pure zinc alloy according to claim 1, characterized in that: The average Zn grain size of the nearly pure zinc alloy is ≤2 μm, and the dislocation density is ≤2×10 14 m -2 ; Keep warm in air atmosphere at 37~200 ℃ for 5 h~100 h, the average size of Zn grains is ≤10 μm.
4. The high performance near-pure zinc alloy according to claim 1, characterized in that: The smelting process of the near-pure zinc alloy uses the pure metal corresponding to each element in the near-pure zinc alloy as raw materials, wherein the raw material Zn is pure zinc with a purity greater than 99.99%, and is smelted 3 to 10 times under vacuum or inert gas protection to obtain a near-pure zinc alloy ingot.
5. The high performance near-pure zinc alloy according to claim 4, characterized in that: The smelting conditions of the near-pure zinc alloy are as follows: the principle of selecting the crucible material is to select a ceramic material with a melting point at least 800°C higher than that of pure zinc, and the alloy is smelted in an Al2O3 ceramic crucible with a melting point higher than 2000°C; the smelting is carried out in two steps, firstly heating to 480-550°C, keeping warm for 1-3 min, and then cooling to 420-460°C, keeping warm for 1-5 min.
6. The high performance near-pure zinc alloy according to claim 4, characterized in that: During the smelting process, the frequency of electromagnetic stirring is 800-3000 HZ; during the smelting process, at least one melt covering agent selected from KCl, NaCl, MgCl2, LiCl and borax is added.
7. The high performance near-pure zinc alloy according to claim 1, characterized in that: The heat treatment is at least one of homogenization heat treatment, solution heat treatment, aging heat treatment, and double-stage aging heat treatment.
8. The high performance near-pure zinc alloy according to claim 7, characterized in that: The heat treatment includes but is not limited to the following two methods: (1) Solution heat treatment first, followed by aging heat treatment; (2) Solution heat treatment is performed first, followed by two-stage aging heat treatment.
9. The high performance near-pure zinc alloy according to claim 8, characterized in that: The temperature of the solution heat treatment is 300-360°C, and the temperature is kept for 8-20 hours; The aging heat treatment temperature is 50 to 180°C, and the heat preservation time is 0.1 to 12 hours; The first stage aging heat treatment of the double-stage aging heat treatment has a temperature of 50-80°C and a holding time of 5 min-6 h, and the second stage aging heat treatment has a temperature of 100-150°C and a holding time of 5 min-10 h. The cooling method after the heat treatment is any one of air cooling, furnace cooling, water quenching and oil quenching.
10. The high performance near-pure zinc alloy according to claim 1, characterized in that: The large plastic deformation is selected from at least one of groove rolling, equal-channel angular extrusion, high-pressure torsion, and high-speed impact.
11. The high performance near-pure zinc alloy according to claim 1 or 10, characterized in that: The temperature of the large plastic deformation is -50 to 320°C, and the temperature is kept for 15 minutes to 3 hours before deformation.
12. The high performance near-pure zinc alloy according to claim 10, characterized in that: During the groove rolling, the rolling speed is 0.05-0.6 m / s; the deformation of a single pass is 20%-28%, and the total deformation is 98%-99%; During the equal-channel angular extrusion, the corresponding extrusion passes are 10 to 25, the extrusion speed is 1 to 20 mm / s, and the total deformation is 98% to 99.7%; During the high-pressure twisting, the applied pressure is 0.5 to 6 GPa, the number of deformation circles is 2 to 6 circles, and the twisting speed is 0.3 to 2 r / min; During the high-speed impact, the impact speed is 10-100 m / s, the impact load is 100-1000 N, the impact angle is 45-60°, and the impact time is 0.1-1 s.
13. The high performance near-pure zinc alloy according to claim 1, characterized in that: The rapid cooling method after the large plastic deformation is any one of quenching in a water bath, an oil bath, and liquid nitrogen.
14. An application of the high performance near-pure zinc alloy according to any one of claims 1 to 13, characterized in that: The alloy can be applied to degradable stents, intestinal, vascular or neural anastomosis devices or staples, vascular clips, guided tissue regeneration membranes, artificial heart valves, meningeal repair membranes, soluble bridge plugs for oil drills, soluble fracturing balls, electrogalvanized materials, building zinc materials, battery zinc materials, printing zinc materials, and zinc-based alloy solder preparation.